Management of serotonergic syndrome in a critically Ill patient after suicide with polypharmacy - GÜL, FETHİ (My University, 2023)
Introduction: Serotonin syndrome is a life-threatening drug reaction that results in neuromuscular dysfunction and mental status changes due to intoxication and drug interactions. Hemoadsorption devices are potential therapeutic tool for intoxication due to their highly efficient elimination capacity of endogenous and exogenous hydrophobic substances. In this case, we aimed to present effect of extracorporeal supportive treatment in a patient who developed serotonergic syndrome due to Selective Serotonin Reuptake Inhibitor (SSRI) drug overdose.Case: A 34-years old female patient without a past medical history was admitted to the intensive care unit from the emergency department with the diagnosis of drug intoxication. She had taken pregabalin 75 mg (n=41), duloxetine 60 mg (n=22) and tramadol 100 mg (n=17) orally. Upon admission to the emergency service her Glascow Coma scala was 15 and arterial blood gases showed both respiratory and metabolic acidosis (pH: 7.19, lactate: 4.4 mmol/L, PO2: 75 mm/Hg, PCO2: 50 mmHg, HCO3: 18.2, BE: -9). She was intubated due to progressive dyspnea and tendency to sleeping and the coma. Physical examination revealed myoclonic contractions in the proximal upper and lower extremities, and serotonergic syndrome was considered using as Hunter’s criteria. Cyproheptadine, a specific serotonin antagonist, was used as an antidote. Due to the development of metabolic acidosis and ongoing intermittent contractions, dialysis treatment was applied for two days with simultaneously carbon filter. Dialysis treatment was terminated on the 3rd day and the patient was extubated. No myoclonic contraction was observed during the following days and the patient was discharged to the ward on the 5th day of the intensive care unit.Discussion: Serotonin syndrome can result in significant morbidity and mortality including acute encephalopathy, renal failure and cardiac arrest. In addition to supportive treatments and antidotes, hemofiltration and hemoabsorption treatments are used especially in complicated cases. In our patient, rapid clinical recovery was achieved after simultaneous CRRT and hemoadsorption treatments which was used due to persistent myclonus despite use of special antidote cyproheptadine.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery; Serotonergic syndrome; hemoadsorption; carbon filter; intoxication